Quality Assurance Management of Schools in the Digital Era under Nonthaburi Primary Educational Service Area Office 2 - Mangmee, Sunanthanee; Panjarattanakorn, Darunee (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to 1) examine the implementation of internal quality assurance in schools under the Nonthaburi Primary Educational Service Area Office 2 in the digital era, and 2) compare the implementation of internal quality assurance in schools under the Nonthaburi Primary Educational Service Area Office 2 in the digital era, classified by gender, age, educational attainment, work experience, and school size. The sample consisted of 285 respondents selected through stratified random sampling based on school size. The research instrument was a questionnaire with item-level content validity indices ranging from 0.67 to 1.00 and an overall reliability coefficient of 0.89. The statistical methods used for data analysis included frequency distribution, percentage, mean, standard deviation, t-test, one-way ANOVA, and LSD post hoc test. The research findings revealed that 1) the overall and aspect-specific levels of internal quality assurance implementation in schools under the Nonthaburi Primary Educational Service Area Office 2 in the digital era were at the highest level 2) teachers with different genders, educational backgrounds, work experiences, and school sizes did not significantly differ in their opinions on the implementation of internal quality assurance. However, teachers of different age groups demonstrated statistically significant differences in their opinions at the .01 level.